Beat‐to‐beat variability of fetal myocardial performance index. (August 2017) - Maheshwari, P.; Alphonse, J.; Henry, A.; Wang, J.; Redmond, S. J.; Welsh, A. W.
ABSTRACT: Objectives: To determine whether there is beat‐to‐beat (BTB) variability in the fetal left myocardial performance index (MPI), as evaluated by an automated system, and whether there is a correlation between MPI and fetal heart rate (FHR). Methods: This was a prospective cross‐sectional study of uncomplicated, morphologically normal, singleton pregnancies at 20–38 weeks' gestation. Multiple cineloops for left MPI measurement were acquired during a single examination of each fetus. Raw cineloop data were analyzed by our automated MPI system (intraclass correlation coefficient of 1.0 for any given waveform) to produce a set of MPIs. The corresponding instantaneous FHR was measured for each individual cardiac cycle for which MPI was calculated. Results: Data from 29 fetuses were analyzed; mean MPI was 0.52, mean FHR was 150 beats per min and the median number of cardiac cycles examined per fetus was 70 (interquartile range, 31–115). Marked BTB variability was noted; median coefficient of variation was 10% (range, 5.5–13.9%). FHR was weakly correlated with absolute MPI ( r = 0.22; P < 0.05). BTB variation in MPI as a percentage of the mean MPI was not significantly correlated with FHR ( r = 0.031; P = 0.146). When standard error of the mean of all MPI values was divided by the mean for each case, it showed that at least four cardiac cycles should be averaged to reduce MPI variability to approximately ± 5%. Conclusion: There is significant BTB variability in fetal left MPI, which has an overall weak correlation with FHR. This could be a factor affecting the consistency of MPI values reported by different research groups. Variability would be reduced by averaging 4–5 cardiac cycles per fetus. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd.